2006
DOI: 10.1071/en05050
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Zinc and Cadmium Phytoavailability Within a Contaminated Agricultural Site using DGT

Abstract: Environmental Context.In some agricultural areas, soils are contaminated by trace elements. This contamination of cultivated soils may constitute a serious problem for human health through the accumulation of metals in the edible parts of crops. In order to assess the risk for human health associated with metal contamination of soil, we need to develop simple tools like Diffusive Gradients in Thin Films (DGT) for predicting crop metal accumulation. The present study focuses on an agricultural site contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Zinc content in cress (Lepidium sativum L.) shoots was larger in acidic soils (pH≈5) than in neutral soils (Zhang et al 2004), while Zn and Cd contents in lettuce (Lactuva sativa L.) shoots increased with decreasing pH in a range of contaminated soils (Cornu and Denaix 2006). Lexmond (1980) also noted a decrease in shoot Cu content of field-grown maize (Zea mays L.) with increasing soil pH, but to a much smaller extent than the decrease in free Cu 2+ concentration.…”
Section: Introductionmentioning
confidence: 97%
“…Zinc content in cress (Lepidium sativum L.) shoots was larger in acidic soils (pH≈5) than in neutral soils (Zhang et al 2004), while Zn and Cd contents in lettuce (Lactuva sativa L.) shoots increased with decreasing pH in a range of contaminated soils (Cornu and Denaix 2006). Lexmond (1980) also noted a decrease in shoot Cu content of field-grown maize (Zea mays L.) with increasing soil pH, but to a much smaller extent than the decrease in free Cu 2+ concentration.…”
Section: Introductionmentioning
confidence: 97%
“…The extractants were 0.11 mol·L −1 HAc [27,29], 0.05 mol·L −1 EDTA and 0.01 mol·L −1 CaCl 2 [28,30]. Among the three methods, the 0.11 mol·L −1 HAc was the first step in a three-step sequential extraction procedure recommended by the European Community Bureau of Reference (BCR) [27,31,32,33].…”
Section: Methodsmentioning
confidence: 99%
“…A number of researchers contend that DGT-measured concentrations of Cd in soils were not well correlated with Cd concentrations in wheat [24], lettuce [25] and ryegrass [26] and the previous experimental results indicated that the DGT was not a robust tool for evaluating the Cd bioavailability; its measured labile concentrations were easily influenced by the species of accumulated biota and the physicochemical properties of soils [27,28,29]. As we know, different growth periods accounted for the different rate of uptake, but the DGT mimic the uptake processes mechanically.…”
Section: Introductionmentioning
confidence: 99%
“…Pot trials have shown good correlations between plant metal uptake and metals measured in contaminated soils by DGT (Zhang et al 2001;Davison et al 2000;Zhang et al 2004). Plant Zn concentration was highly correlated with Zn determined by DGT in soil, and it has therefore been suggested that DGT is a sensitive tool to assess Zn phytoavailability in contaminated agricultural soils (Cornu and Denaix 2006). DGT has been used to assess the potentially bioavailable metal directly in soils in the field (Nowack et al 2004).…”
Section: Introductionmentioning
confidence: 98%